Production technique–structure relationship in bioceramic-coated scaffold applications - Aslan, Naim; Topuz, Mehmet; Aksakal, Bunyamin; Dikici, Burak (Elsevier, 2023)
It is well known that the surface of metal-based implants is very resistive in aggressive body environments due to the noble oxide layer naturally formed on their surfaces. However, their osseointegration properties are very low. By the way, specific cells attached are desired on the implant surface when the surface of an implant connects with tissue in many circumstances. Thus in parallel with technological developments, biomedical engineering focuses on the growth of new tissue on the implant surface or in the porosities of the implant. The bulk properties of metallic scaffolds, especially Young’s modulus, can be controlled by the porosity ratio of the scaffold but cannot form a bond between the implant and tissue interfaces. Thus the coating of scaffold walls with a bioactive material is required. In this chapter, bioceramic coating techniques of scaffolds, mechanical and corrosion behavior, biocompatibility, and interactions of surface/tissue interface, especially considering the last published reports, were reviewed, in detail. © 2023 Elsevier Ltd. All rights reserved.
Keywords: bioceramic coating; biocompatibility; mechanical properties; Scaffold; surface modification